Pengaruh Kompensasi, Lingkungan Kerja Dan Budaya Perusahaan Terhadap Kepuasan Kerja Karyawan Pada Perusahaan Daerah Air Minum Kota Malang - Muhammad Zamanudin; Nurhajati Nurhajati; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractBased on research carried out with the aim of analyzing the effect of compensation, work environment, and corporate culture on employee job satisfaction in Malang Municipal Water Supply Company. The population used in this study were all employees of the Municipal Water Supply Company of Malang City, amounting to 338 employees from December 2019 to January 2020. The sampling technique used was purposive sampling where the technique to ensure the research sample with certain assessments intended to make the data generated can be used as an example or representative. The method used is multiple linear regression analysis with hypothesis testing using the t test and f test. From this study produced answers that have been previously processed that simultaneous compensation, work environment and company culture influence employee job satisfaction which justifies H4. Compensation has a significant effect on employee job satisfaction partially and justifies H1. The work environment has a significant effect on employee job satisfaction partially and justifies H2. Corporate culture has a significant effect on employee job satisfaction partially and justifies H3. Key Words :(Compensation, Work Environment, Corporate Culture, Employee Job Satisfaction).